Comparison of agarose gel and capillary zone electrophoresis methods with preliminary reference interval generation using capillary zone electrophoresis in bald eagles (Haliaeetus leucocephalus) - da Fonseca, Leandro Abreu (Veterinary clinical pathology, 2023)
© 2023 American Society for Veterinary Clinical Pathology.